Magnitude and Spread of Bed Bugs (Cimex lectularius) throughout Ohio (USA) Revealed by Surveys of Pest Management Industry - Susan C. Jones (Insects, 2021)
Bed bugs have recently re-emerged as human pests worldwide. In this study, two surveys queried licensed pest management companies in Ohio (Midwest USA) about their experiences managing bed bugs. A primary objective was to assess the magnitude and spread of bed bug infestations statewide based on companies’ treatment records from 2005 and 2011 (first survey) and 2016 (second survey). The survey response rates were 35.6% and 31.6%, respectively. Treatment data from 2005 indicated that Ohio’s bed bug problem likely started in the SW corner of the state in Hamilton County (includes city of Cincinnati), since it totaled five times more treatments (approximately 4500) than second-ranking, centrally located Franklin County (Columbus). In the first half of 2011, more than 15,000 treatments were performed in these two counties. In 2016, treatments reached nearly 38,000 in Franklin County and in NE Ohio in the three combined counties that include Cleveland-Akron-Canton. Bed bug problems expanded statewide during an 11 y period, with an estimated 100+ treatments in 7 counties in 2005, 45 counties in 2011, and nearly all 88 counties in 2016. Apartments/condos and single-family residences comprised the largest share of bed bug work. Residents misused many pesticides and household cleaners trying to eliminate bed bugs. Many also discarded unwrapped infested furniture, which may further spread these bugs. More public education is needed to stop such practices. This study shows that bed bug problems grow and spread quickly; federal, state, and local officials and the public should immediately deal with bed bugs.